Mikkel Rytter: Family Upheaval. Generation, Mobility, and Related- ness among Pakistani Migrants in Denmark. Oxford: Berghahn Books 2013. 234 sider. ISBN 978-0-85745-939-8. Pris: 75. - Vacher, Mark (Tidsskriftet Antropologi, 2014)
Intet resumé